1972
DOI: 10.1007/bf01074443
|View full text |Cite
|
Sign up to set email alerts
|

Minimal cues in the vocal communication of affect: Judging emotions from content-masked speech

Abstract: Vocal expressions of emotions taken from a recorded version of a play were contentmasked by using electronic filtering, randomized splicing and a combination of both techniques in addition to a no-treatment condition in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
3

Year Published

1974
1974
2023
2023

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 18 publications
4
58
0
3
Order By: Relevance
“…Argyle and his colleagues (Argyle, Salter, Nicholson, Williams, & Burgess, 1970) found that 22 times more variance is accounted for by the tone of one's voice than by the content of the utterance when people are asked to interpret utterances. In fact, even when the content of recorded utterances is nearly completely obliterated by means of electronic masking, filtering, or random splicing of the tape, subjects still can encode the emotions expressed in these utterances quite reliably (Dawes & Kramer, 1966;Scherer, Koivumaki, & Rosenthal, 1972). And we have no difficulty in identifying emotions expressed by members of unknown cultures speaking unknown languages.…”
mentioning
confidence: 99%
“…Argyle and his colleagues (Argyle, Salter, Nicholson, Williams, & Burgess, 1970) found that 22 times more variance is accounted for by the tone of one's voice than by the content of the utterance when people are asked to interpret utterances. In fact, even when the content of recorded utterances is nearly completely obliterated by means of electronic masking, filtering, or random splicing of the tape, subjects still can encode the emotions expressed in these utterances quite reliably (Dawes & Kramer, 1966;Scherer, Koivumaki, & Rosenthal, 1972). And we have no difficulty in identifying emotions expressed by members of unknown cultures speaking unknown languages.…”
mentioning
confidence: 99%
“…Ekman, 1972;Scherer et al, 1972;Scherer, 1974a) and that (2) types of cues r e s u l t i n g in d i s c r e p a n t inferences may occur jointly in a sample of behavior. More research to support these assumptions is clearly called for.…”
Section: Introductionmentioning
confidence: 99%
“…This view obviously does not exclude the possibility of short-term influences of autonomic arousal on the voice organs affecting voice quality, as for example in highly emotional states such as fear or anger (cf. Scherer et al, 1972). Stable or habitual voice quality, however, may well be an independent rather than a dependent variable in personality formation and behavior.…”
Section: Discussionmentioning
confidence: 99%